Exploring the Therapeutic Potential of Kalanchoe Pinnata: A Comprehensive Analysis of Bioactive Compounds and Pharmacological Activities - Bhusal, Dakshina; Poudel, Manila; Tamang, Ashika; Dhital, Sujan; Parajuli, Nirmal; Shrestha, Timila; Bharati, Samjhana; Maharjan, Binita; Adhikari Subin, Jhashanath; Marasini, Bishnu Prasad; Shrestha, Ram Lal Swagat (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Natural products are vital in drug discovery for their bioactive compounds. This study evaluated Kalanchoe pinnata's leaf extracts for antidiabetic, antimicrobial, antioxidant, and cytotoxic properties. GC-MS identified seven components in hexane and twenty in methanol extracts. The ethyl acetate extract had high phenolic (485.17 mg GAE/g) and flavonoid (40.25 mg QE/g) contents. Methanol extract showed strong antioxidant (IC50: 293.53 µg/mL) and anti-alpha glucosidase (IC50: 195.39 µg/mL) activity. Antimicrobial tests showed varied effectiveness, while chloroform and acetone extracts exhibited notable cytotoxicity. ADMET predictions assessed absorption and blood-brain barrier penetration, highlighting K. pinnata's potential for drug development.